Persepsi Ulama Dayah Terhadap Konversi Bank Konvensional (Studi Kasus Di Kota Banda Aceh) - Arifin, Muhammad; Usman, Ismuadi; Fadhillah, Alfatan (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
After the conversion of conventional banks to sharia banks, people still think that there are no significant differences in the operational system of sharia banks except just changing the name, changing the term interest to profit sharing and several other small things that are not significant. This research aims to analyze the perceptions of ulama regarding the conversion of conventional banks to sharia banks in Banda Aceh. This research uses descriptive qualitative methods. Data was obtained by interviewing related parties such as ulama and community leaders. The research results show that according to the perception of ulama, the conversion of conventional banks to sharia banks is in accordance with the Islamic banking system because there is a Sharia Supervisory Board, although it still requires improvement. According to them, this conversion is the right thing and indeed should be carried out considering the existence of the Qanun on Sharia Financial Institutions in Aceh.